Nanofios de germânio : síntese, caracterização estrutural, propriedades elétricas e aplicações - Gouveia, Riama Coelho (Universidade Federal de São Carlos, 2016)
The element germanium is part of the history of electronic equipment based on semiconductor from its early days with the invention of the transistor, until today with current research related to growth of germanium nanowires and their application in devices such as transistors, sensors, solar cells, etc. Different experimental methods can be used for obtaining germanium nanowires. Among these, one of the most widely used and efficient is the vapor-liquid-solid mechanism, in which vapor phase germanium is adsorbed onto a liquid seed metal catalyst, usually gold, and then precipitated at the liquid-solid interface, resulting in the nanowire. Although the metal has only the catalyst function, some atoms may diffuse along the nanowires and affect their properties. Then, one of the aims of this work was to synthesize germanium nanowires by the vapor-liquid-solid method with the use of five different catalysts – gold, silver, copper, indium and nickel – and verify the influence of the metal on structural properties of the nanowires. As result of this stage it was found that is possible to obtain nanowires basically composed of single crystalline germanium with diamond structure, without apparent defects, having long-range order and with length/ diameter ratio of 103, using all the tested metals. Also in this stage it was observed that the metal catalyst had an influence on: the settings of synthesis process, such as the temperature of the heat treatment and the synthesis temperature, and consequently in the germanium oxide around the nanowires; the diameters and diameter distributions of the nanowires, that lead to phonon confinement effect in nanowires with small diameters grown using nickel. Regarding applications, the current interest in germanium is justified by some of its properties such as high carrier mobility (electrons and holes), small values of indirect (0,66eV) and direct (0,8eV) energy gaps associated with high absorption coefficient of electromagnetic radiation in visible an infrared wavelength, and a large excitonic Bohr radius which highlights quantization effects. Thus, another objective of this research was to investigate electrical and optoelectronic characteristics of the produced germanium nanowires, constructing single nanowire devices and nanowire networks devices. The results of this part showed that: all the devices presented the semiconductor behavior expected for single crystalline germanium; the metal-semiconductor contact behavior – ohmic or Schottky – depended on the synthesis temperature and for the Schottky contacts, an insulating layer on the metal-nanowire interface, probably composed by germanium oxide, caused an increasing linear dependence of the barrier height with temperature; both thermal activation mechanism as well as variable range hopping were observed in germanium nanowire network devices, since small differences in diameter or on the surface of the nanowires can change the dominant transport mechanism, due to the large surface/ volume ratio of these nanostructures; the photoconductor and the photodiode constructed with germanium nanowire network presented photo-response in a wide range of illumination power in visible and infrared light wavelengths. Finally, complementing this PhD program, the activities of science dissemination developed at the IFSP campus Sertãozinho prepared this institution for scientific research in physics and showed the first results both in physics as in the physics teaching; motivating high school and college students to continue their studies.
Keywords: Germânio; Nanofios; Propriedades estruturais; Caracterizações elétricas; Germanium; Nanowires; Structural properties; Electrical characterization; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL